Physical and Mechanical Properties of Gypsum-Like Rock Materials - Sijiang Wei; Chongyang Wang; Yushun Yang; Meng Wang (Advances in Civil Engineering)
In the process of tunnel construction, gypsum rock is often encountered, and the volume of gypsum rock expands when encountering water, which is easy to cause the occurrence of rock fall, collapse, and other disasters, bringing serious challenges to the safe construction of the tunnel. Therefore, in this paper, four groups of samples under different moisture content are tested by ultrasonography, uniaxial compression, conventional triaxial compression, Brazilian splitting, X-ray diffraction, and SEM, and then the physical and mechanical properties of gypsum rock are studied, and the conclusion is as follows: the density of the water saturated sample, and the longitudinal wave velocity of the natural sample are the highest. Both the water saturation and dehydration conditions have a weakening effect on the remolded sample of high-strength gypsum powder. The peak intensity of the sample gradually increases with the increase of confining pressure, and the relationship between the peak intensity and confining pressure of the sample conforms to the Coulomb strength criterion. After high-temperature dehydration, the sample showed obvious plastic softening characteristics. The cohesion and internal friction angle of the sample are closely related to the water content. The cohesion is the largest in the 45°C dehydrated sample, the internal friction angle is the smallest in the saturated sample, whereas the cohesion is the smallest and internal friction is the largest in the high-temperature dehydrated sample. The characteristics of failure for the natural and 45°C dehydrated samples are almost the same and most samples show shear or shear-tensile failure. The shear plane begins at the edge of the end face of the sample and exhibits a typical diagonal shear failure. The high-temperature dehydrated samples are completely broken under uniaxial and triaxial compression conditions. After high-strength gypsum powder was used to make the remolded sample, the calcium sulfate disappeared, the water content increased, and the main mineral components of the natural and saturated samples were the same. After dehydration at 45°C, the sample began to release structural water and generate SiO2. After high-temperature dehydration, the hemihydrate gypsum continued to dehydrate and become soluble anhydrous gypsum.